Rhizobacteria alter the phytoremediation potential and antibacterial activity of lemongrass essential oil in lead-contaminated soils - da Cruz, Rayane Monique Sete [UNESP]; Pinc, Mariana Moraes; de Almeida Cardoso, André; Ferreira, Henrique [UNESP]; Brienzo, Michel [UNESP]; Alberton, Odair (Elsevier, 2025)
Lead (Pb) is one of the most harmful soil contaminants affecting plant growth. Cymbopogon citratus (lemongrass) stands out due to its essential oil rich in citral. Studies indicate that Azospirillum brasilense stimulates the development of lemongrass, optimizing nutrient uptake. The methodology involved a factorial greenhouse experiment using lemongrass grown in Pb-contaminated soil, with or without inoculation by A. brasilense (strains Ab-V5 and Ab-V6), and included evaluations of plant growth, Pb and nitrogen content, nitrate reductase activity, essential oil composition, and antibacterial activity. This study tested the effects of A. brasilense in soils with different Pb concentrations, analyzing growth parameters and essential oil composition. The results showed that lemongrass exhibited favorable root development at Pb concentrations up to 300 mg kg−1, and A. brasilense improved nitrogen fixation and stress tolerance. The essential oil of lemongrass, free of Pb contamination, contains high levels of neral and geranial and demonstrated bactericidal activity against Xanthomonas citri and inhibitory effects on X. vesicatoria. These findings suggest that lemongrass oil can be used in biological pest control, highlighting its potential for sustainable applications in the cosmetic and natural disinfectant industries.